Challenges in Cloud Computing Adoption for SMEs in the Middle East - Fatma Abudaqqa (European Scientific Journal, ESJ, 2025)
Technology's growth significantly affects how businesses grow because it offers new ways to do business. Due to a sharp rise in market competition and a rapidly changing business environment, businesses in all industries and sectors utilize information and communication technologies (ICTs) to enhance their company operations and boost their value. This study aims to address the challenges that prevent small and medium-sized businesses in the Middle East from adopting cloud computing, as well as the generally accepted techniques for eliminating these challenges. The study utilized a systematic review of relevant literature. The inclusion and exclusion criteria, as well as the analytic procedure, were documented in the study using the PRISMA protocol. The study also looked for pertinent journal publications that employed mixed, qualitative, and quantitative research methodologies using three pertinent databases: Sustainability, Google Scholar, and Emerald. The included English-language publications had to have been released between the first quarter of 2023 and 2016. More significantly, the evaluation did not include any research that did not concentrate on SMEs in the Middle East. Following an extensive analysis of the literature, it was discovered, among other things that infra needs to be more, budgetary restrictions, and a need for increased understanding of the significance of Industry 4.0.  In conclusion, SMEs face challenges in adopting cloud computing, including financial constraints, restrictive policies, security concerns, and fear of losing investments in existing infrastructure, amongst others. Addressing these issues through policy changes, competition, and tailored solutions can enhance cloud adoption and SME competitiveness.